2009
DOI: 10.31729/jnma.230
|View full text |Cite
|
Sign up to set email alerts
|

Need of Improvement in Emergency Medical Service in Urban Cities

Abstract: Introduction: An effective Emergency Medical Service system does not exist in Nepal. For an effective EMS system to be developed the scale of the problem and the existing facilities need to be studied. Methods: Prospective observational study was carried out on 1964 patients attending Emergency Department at Patan Hospital during one month period of September 2006. The patients were specifically enquired on mode of transport used, place of origin and whether they called for an ambulance or not. Patients triage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…11 Our study showed 43.2% patients arriving in ambulance which is slightly higher than the services availed by patients (13.4% and 9.4%) in previous studies done in Nepal. 4,12 Patients who arrived in ambulance with a triage score of 2 (sick patients) was 27.6% which have improved from 15.4% by Gongol et al Improvement in the proportion of using ambulance service is observed among the Nepalese population in the last decade. This study also showed an increased use of ambulance service in the eastern part of Nepal in comparison to studies done in Kathmandu.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…11 Our study showed 43.2% patients arriving in ambulance which is slightly higher than the services availed by patients (13.4% and 9.4%) in previous studies done in Nepal. 4,12 Patients who arrived in ambulance with a triage score of 2 (sick patients) was 27.6% which have improved from 15.4% by Gongol et al Improvement in the proportion of using ambulance service is observed among the Nepalese population in the last decade. This study also showed an increased use of ambulance service in the eastern part of Nepal in comparison to studies done in Kathmandu.…”
Section: Discussionmentioning
confidence: 92%
“…Ambulance services availed by patients in eastern Nepal were still unreliable and not preferred even after a decade of previous studies done in Nepal. 4,10 Preference towards private vehicles to reach hospital is also prevalent. The EMS service is currently available in Kathmandu valley by Nepal ambulance services but yet to be expanded outside the valley.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Innovations in education ( Adhikari N, 2010 ; Butterworth, 2010 ; Butterworth & Hayes, 2010 ; Butterworth, Hayes & Neupane 2008 ; Butterworth, Hayes, & Zimmerman, 2011 ; Butterworth & Pradhan, 2010 ; Upadhyay, Bhandary, & Ghimire, 2011 ) and health policy ( Allaby, 2003 ; Gongal et al, 2009 ; Gongal & Bhattarai, 2005 ; Gongol & Maharjan 2010 ; Hari, Mark, Bharati, & Khadka, 2007 ; Hayes, 2008 ) have been two other areas of publishing strength for the institution. The hospital also has been a source of telemedicine expertise for more than ten years ( Graham et al, 2003) .…”
Section: Introductionmentioning
confidence: 99%